√-9 √-4 is equal ton
Answers
Answered by
0
Hey as we all know √a * √b = √a*b , but let's add little more knowledge to it.
The above mathematical equation (or rule) holds true only and only when atleast one of them is non-negative.
Now back to the given problem , here both are negative numbers {-9 , -4} . None of them are non-negative.
So we can't apply that rule here.
Therefore , √-9 *√-4 = √36 = {6 , -6 }will not give us proper answer.
And we also know √-1 = i (iota) which means
i^2 = -1
Now √-9 = 3i & √-4 = 2i
Now 3i * 2i = 6 i^2 = -6
√-9 *√-4 = -6.
So now we need to simplify them using complex numbers.
Similar questions